Why can't I?

Calculus Level 2

lim x π π + x cos ( x ) x π \large \lim_{x \to \pi} \frac{\pi+x\cos(x)}{x-\pi}

Evaluate the limit above without using L'Hospital's Rule.


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Dec 25, 2015

Let f ( x ) = x cos x f(x) = x\cos x , then lim x π x cos x ( π ) x π = lim x π f ( x ) f ( π ) x π = f ( π ) = cos π π sin π = 1 \displaystyle \lim_{x \to \pi} \dfrac{x\cos x - (-\pi)}{x-\pi} = \lim_{x \to \pi} \dfrac{f(x) - f(\pi)}{x-\pi}= f'(\pi) = \cos \pi - \pi \sin \pi = \boxed{-1}

lim x π π + x cos ( x ) x π = l i m x π π x x π = 1 \large \lim_{x \to \pi} \frac {\pi + x\cos(x)}{ x - \pi} = lim_{x \to \pi} \frac {\pi - x}{x - \pi} = \boxed{-1}

Using Taylor serie for cos x \cos x around x = π x = \pi

Majed Musleh
Jun 15, 2015

lim x π π + x cos ( x ) x π × π x cos ( x ) π x cos ( x ) \lim_{x \to \pi}\frac{\pi+x\cos(x)}{x-\pi}×\frac{\pi-x\cos(x)}{\pi-x\cos(x)} = > => lim x π π 2 x 2 cos 2 ( x ) ( x π ) ( π x cos ( x ) ) \lim_{x\to \pi}\frac{\pi^{2}-x^{2}\cos^{2}(x)}{(x-\pi)(\pi-x\cos(x))} = > lim x π π 2 x 2 + x 2 x 2 cos 2 ( x ) ( x π ) ( π x cos ( x ) ) => \lim_{x \to \pi} \frac{\pi^{2}-x^{2}+x^{2}-x^{2}\cos^{2}(x)}{(x-\pi)(\pi-x\cos(x))} = lim x π π 2 x 2 ( x π ) ( π x cos ( x ) ) + lim x π x 2 ( 1 cos 2 ( x ) ( x π ) ( π x cos ( x ) =\lim_{x \to \pi}\frac{\pi^{2}-x^{2}}{(x-\pi)(\pi-x\cos(x))}+\lim_{x \to \pi}\frac{x^{2}(1-\cos^{2}(x)}{(x-\pi)(\pi-x\cos(x)} = lim x π x π ( x + π ) x π ( π x cos ( x ) ) + lim x π x 2 sin ( x ) sin ( x ) ( x π ) ( π x cos ( x ) ) =\lim_{x \to \pi} \frac{-\boxed{x-\pi}(x+\pi)}{\boxed{x-\pi}(\pi-x\cos(x))}+\lim_{x \to \pi}\frac{x^{2}\sin(x)\sin(x)}{(x-\pi)(\pi-x\cos(x))} = 2 π 2 π + lim x π sin ( x ) x π × lim x π x 2 sin ( x ) π x cos ( x ) =\frac{-2\pi}{2\pi}+\lim_{x \to \pi}\frac{\sin(x)}{x- \pi}×\lim_{x \to \pi} \frac{x^{2}\sin(x)}{\pi-x\cos(x)} = 1 + lim x π sin ( π x ) ( π x ) × ( 0 ) =-1+\lim_{x \to \pi} \frac{\sin(\pi-x)}{-(\pi-x)}×(0) = 1 + ( 1 × 0 ) =-1+(-1×0) = 1 =\boxed{-1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...